Pentingnya Media Pembelajaran Untuk Meningkatkan Etos Belajar Siswa Pada Mata Pelajaran PAI SMKN 1 Cikarang Barat - Aziz, Abdul; Hambali, Yoyo; Asiah, Siti; Fitria, Mawaddatul; Fitriani, Mustika; Rosyadi, Imron (Jurnal Ilmiah Wahana Pendidikan, 2024)
Learning has encountered misfortunes as confirmed by the decline in understudies' learning ethos. This also happened to understudies at SMKN 1 Cikarang Barat while studying PAI. Understudy field execution practice is a conversation to additionally foster the understudy learning environment by using innovative learning media. The learning media given by these understudies has created results where numerous understudies are beginning to be energetic about taking part in PAI learning in class. The preparation was held from 04 September 2023 to 22 November 2023 at SMKN 1 Cikarang Barat, Bekasi State, West Java, including 7 understudies from the Islamic Severe Schooling and Preparing Division, Islamic School 45 Bekasi. Seeing the outcomes of this help, just regular learning media can give new impressions to understudies and further foster understudies' learning ethos. This is exhibited by the excitement and energy shown.